Flexible office, flexible working? A post-relocation study on how and why university employees use a combi-office for their activities at hand. (4th May 2020) - Cobaleda-Cordero, Antonio; Babapour, Maral; Karlsson, MariAnne
This study reports on a group of university employees, six months after their relocation from cell-offices into a combi-office. Data from interviews, observations and planning documentation was collected to gain an in-depth understanding of how employees use their office landscape and why. Activity theory was taken as framework for the analysis. The findings show that the new office landscape was perceived to be more flexible and capable of supporting employees' activities. The overall occupancy was low and backup spaces, such as quiet rooms, were barely used. Matches and mismatches between the employees, their activities and the office were identified that explain the occupancy rates and why spaces such as quiet rooms were unpopular spaces. This paper contributes with rich detail on the use of a flexible office landscape in a university context and shows the usefulness of activity theory in the study of employee-office interactions.